Enhancement of Skin Pigmentation and Intestinal Health in Comet Goldfish (Carassius auratus) Using Dunaliella salina Teodoresco 1905 Supplemented Diets - Wa Iba; Martono Martono; Rukman Awan Syam; Ruslaini Ruslaini; La Ode Baytul Abidin; Agus Kurnia; Indriyani Nur; Michael A Rice (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. Dunaliella salina meal (7–9%) optimally enhanced skin carotenoid deposition in C. auratus. 2. Higher D. salina inclusion improved intestinal morphology and reduced inflammatory lesions. 3. Intestine somatic index stabilized at 7–9%, indicating better digestive efficiency. 4. Survival rates increased with D. salina supplementation due to antioxidant and immunoprotected effects. 5. Microalgal carotenoids show strong potential as functional additives for ornamental fish feed. Abstract Maintaining efficient and stable carotenoid-based pigmentation remains a challenge in aquaculture due to limited dietary carotenoid bioavailability and variable intestinal absorption. Comet goldfish (Carassius auratus) were used as a model species for aquaculture nutrition and digestive physiology to evaluate the effects of natural carotenoid supplementation from microalgae Dunaliella salina on skin pigmentation and intestinal health. This study aims to determine the effect of D. salina meal addition in formulated feed on the carotenoid content of fish skin, growth and survival as well as the intestinal condition of comet goldfish. Experimental feeds were prepared by incorporating D. salina meal into a formulated feed at graded inclusion levels (0, 3, 5, 7, and 9%), where the microalgal meal was homogenized with other feed ingredients, pelleted, and oven-dried before use. The initial weight of experimental fish was 4 ± 1 g. Fish were maintained in 40 × 35 × 35 cm aquaria for 30 days and fed until satiation with six treatments of formulated feed added microalgae meal at 0, 3, 5, 7 and 9 %. Commercial feed was used as control feed and all treatments were in triplicates. The highest final carotenoid content in skin of comet goldfish at 14.82±0.44 mg. g-1 was obtained with addition of 7 % microalgae meal. The highest weight gain was obtained with addition of 5 % microalgae meal at 5.5 g. Normal comet goldfish intestinal morphology was found in those feds on 9 % microalgae meal. Intestinal inflammation was observed in those feds with the addition of 3, 5 and 7 % microalgae meal and control feed. The intestinal somatic index (ISI) value obtained was 1.08-3.06 %. The survival was 100 % in fish fed with the addition of microalgae meal at high percentage from 5-9%. The findings provide practical guidance for developing natural, microalgae-based functional feeds that improve pigmentation efficiency, higher inclusion levels, particularly 9%, were associated with fewer visible intestinal lesions and enhance survival, thereby contributing to more sustainable and economically valuable aquaculture production. We recommend to use 7-9 % of D. salina meal for use in aqua feed to maintain optimal color, growth and survival of ornamental freshwater fish.